2020
DOI: 10.18203/2320-1770.ijrcog20200903
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate endometrial aspiration using Karman’s cannula versus dilatation and curettage in cases of abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding (AUB) is defined as any variation from the normal menstrual cycle such as changes in regularity, frequency, duration of flow or amount of flow. Objective of this study was to compare the adequacy and diagnostic accuracy of endometrial aspiration using Karman’s cannula versus dilatation and curettage in women with abnormal uterine bleeding.Methods: This prospective study was conducted on 250 women with AUB in age group of more than 40 years. In all patients, endometrial asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…Among other studies which compared Karman with others, Tomar et al . [ 1 ] reported that Karman cannula had a sensitivity of 92.3%, specificity of 100%, PPV of 100%, and NPV of 99.56% for diagnosis of endometrial pathology, which was slightly higher than that of our study.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Among other studies which compared Karman with others, Tomar et al . [ 1 ] reported that Karman cannula had a sensitivity of 92.3%, specificity of 100%, PPV of 100%, and NPV of 99.56% for diagnosis of endometrial pathology, which was slightly higher than that of our study.…”
Section: Discussioncontrasting
confidence: 80%
“…In the present study, one case (0.97%) was inadequate in the Karman cannula group and three cases (2.4%) in the Pipelle group. Among other studies on Karman, the inadequacy rate has been reported to range from 2% to 24%,[ 1 5 10 19 20 21 22 ] and for Pipelle, it has been reported in the range of 2% to 28.8%. [ 13 23 24 25 26 27 ] Since we frequently use Karman cannula, the inadequacy was lower in that group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Previous studies found similar tissue adequacy and similar histopathologic finding between MVA and uterine curettage. [18][19][20][21] Moreover, MVA was reported to have 86.4-96% sensitivity and 100% specificity for diagnosing endometrial pathology. [19][20][21][22][23] MVA has, therefore, been proposed as an alternative technique for obtaining an endometrial biopsy in women with AUB.…”
Section: Introductionmentioning
confidence: 99%